HUBUNGAN ANTARA PERILAKU PENCARIAN INFORMASI KESEHATAN SELAMA PANDEMI COVID-19 TERHADAP KESEHATAN MENTAL MASYARAKAT KECAMATAN SUMBER KABUPATEN CIREBON - Khaifa Ma'sya; Sri Handayani (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
COVID-19 pandemic has a huge impact in multi-sectors mainly in public health. An increase in mental health problems such as anxiety, depression, and trauma has occurred during the COVID-19 pandemic. Misleading information circulating the internet can cause anxiety and panic in society. This study aimed to analyze the correlation of health information-seeking behavior during the Covid-19 pandemic and the mental health of the community of Kecamatan Sumber, Kabupaten Cirebon.This study was quantitative with a cross-sectional study design. The data of this study was collected through interviews. The instrument used a questionnaire Health Information Seeking Behaviour (HISB) and Covid-19 Pandemic Mental Health Questionnaire (CoPaQ). The 100 respondents were selected with the proportion method. The data collection technique was accidental sampling with inclusion criteria that was more than 17 years old and are residents of the Sumber Sub-district. The data analysis method used the Pearson product-moment test.The results showed that 24% of people get information accidentally or not seeking information and most people receive/seek health information during the Covid-19 pandemic through the internet and TV. There were several types of mental health problems suffered by the people of Kecamatan Sumber, Kabupaten Cirebon; they were quality of life (mean=33,6 ; SD=9,373), trauma (mean=4,2 ; SD=2,395), paranoia (mean=4,3 ; SD=1,781), anxiety(mean=13,3 ; SD=5,149), stress (mean=4 ; SD=2,581), and social networks (mean=4,35 ; SD=2,266). The results of the Pearson product-moment test found that there was a correlation of health information-seeking behavior during the Covid-19 pandemic on the mental health of the people of the Sumber Subdistrict, Cirebon Regency (p = 0.000) and the strength of the relation between the two variables was moderate (Pearson correlation = 0.438). People need to be more concerned about mental health problems. They are suggested to improve their mental health by limiting the use of social media, keeping themselves busy with various activities, and maintaining physical health.